Analysis Of Higher Order Thinking Skill (Hots) Problems In Student's Books Theme 3 Class V Elementary School - Sarah Fazilla; Fauziana Fauziana; Paridah Hanum Siregar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The lack of Higher Order Thinking Skills (HOTS) questions in student books causes students to receive inadequate training in solving such questions. This has resulted in the failure to achieve the goals of the 2013 curriculum's learning program, which aimed to equip students with Higher Thinking Skills and 21st-century skills. Therefore, it is important to conduct an analysis of the questions in Class V Student Book Theme 3,